NADPH‐cytochrome P450 reductase mediates the susceptibility of Asian citrus psyllid Diaphorina citri to imidacloprid and thiamethoxam. Issue 2 (2nd November 2020) - Yuan, Chen‐Yang; Jing, Tian‐Xing; Li, Wei; Liu, Xiao‐Qiang; Liu, Tian‐Yuan; Liu, Yi; Chen, Meng‐Ling; Jiang, Rui‐Xu; Yuan, Guo‐Rui; Dou, Wei; Wang, Jin‐Jun
Abstract: BACKGROUND: The Asian citrus psyllid Diaphorina citri has developed high levels of resistance to many insecticides, and understanding its resistance mechanism will aid in the chemical control of this species. Nicotinamide adenine dinucleotide phosphate (NADPH)‐cytochrome P450 reductase (CPR) is crucial in cytochrome P450 function, and in some insects CPR knockdown has increased their susceptibility to insecticides. However, the CPR from D. citri has not been characterized and its function is undescribed. RESULTS: The CPR gene of D. citri ( DcCPR ) was cloned and sequenced. The expression level of DcCPR, determined by reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) analysis, was highest in the midgut and in nymphs. After feeding on double‐stranded RNA for 72 h, the DcCPR messenger RNA level in D. citri adults decreased by 68.4%, and the susceptibility of D. citri to imidacloprid and thiamethoxam significantly increased. Meanwhile, after DcCPR silencing, the specific activities of DcCPR protein and P450s were significantly reduced by 41.6% and 44.7%, respectively. The subsequent western blot analysis and quantification of band intensity also showed that DcCPR content significantly decreased, consistent with the results of the specific activity test. In a eukaryotic expression assay, the viability of cells expressing DcCPR was significantly higher than the viability of cells expressing green fluorescent protein (GFP) when cells were exposed to imidacloprid or thiamethoxam. CONCLUSION: These results indicate that DcCPR contributes to D. citri susceptibility to imidacloprid and thiamethoxam. Abstract : Nicotinamide adenine dinucleotide phosphate (NADPH)‐cytochrome P450 reductase (CPR) gene of Diaphorina citri ( DcCPR ) was initially cloned and sequenced in D. citri . After feeding on double‐stranded RNA for 72 h, the susceptibility of D. citri to imidacloprid and thiamethoxam significantly increased. Meanwhile, after DcCPR silencing, both the specific activities of DcCPR protein and western blot analysis showed that DcCPR content significantly decreased. The subsequent cytotoxicity assay suggested that the viability of cells expressing DcCPR was higher than the viability of cells expressing green fluorescent protein (GFP) when exposed to imidacloprid or thiamethoxam. © 2020 Society of Chemical Industry